Fatores relacionados ao índice de vulnerabilidade clínico-funcional de idosos em seguimento ambulatorial - Barbosa, Gustavo Carrijo (2021)
Introduction: The current scenario in our country shows the growth of the elderly population concomitantly with the increase in the rate of chronic diseases, number of hospitalizations and decline in physical and cognitive abilities. In this sense, the great challenge that is established for health systems is comprehensive care for the elderly user, where Outpatient Care in Gerontology emerges as an effective health strategy in the face of population aging which results in the transition of health status. Objective: To characterize the sociodemographic and health profile of elderly people followed at the Gerontology Outpatient Clinic of HU-UFSCar and to verify the factors related to their Clinical-Functional Vulnerability Index. Method: This is a quantitative and cross-sectional study, conducted with individuals 60 years of age or older, seen at the respective outpatient clinic. Data collection occurred through the application of a protocol containing: characterization, assessment of frailty by the Clinical-Functional Vulnerability Index (CFVI-20), cognitive performance by the 10-Point Cognitive Screener, the degree of dependence on basic activities by the Katz Scale and instrumental activities by the Lawton Scale and evaluation of depressive symptoms by the Geriatric Depression Scale. Spearman's correlation analysis was used to verify the relationship between clinical-functional vulnerability and sociodemographic and health variables. Results: The sample consisted of 50 individuals with a mean age of 79.4 (±9.4) years, of which 70.0% represented women. There was a predominance of widower and average of 3.4 (±3.5) years of schooling. Regarding health, the mean was 3.8 (±2.1) morbidities and 6.1 (±4.4) medications for daily use. Most of the elderly were considered frail, with severe cognitive impairment, a certain degree of dependence on basic and instrumental activities of daily life and absence of depressive symptoms. The statistical analysis showed a moderate correlation between clinical and functional vulnerability and the following variables: age (r=0,380; p=0,006), number of morbidities (r=0,433; p=0,002), number of medications (r=0,514; p=0,000), cognitive function (r=-0,540; p=0,000) and dependence on basic (r=-0,481; p=0,000) and instrumental (r=-0,460; p=0,001) activities of daily living. Conclusions: The sample profile showed a predominance of women, with low schooling, absence of spouse, presence of comorbidities and polypharmacy, factors that may favor higher rates of clinical and functional vulnerability. The correlations observed between CFVI-20 and age, number of morbidities and medications, cognitive performance, and dependence on activities of daily living raise reflections about possible strategies for remission of these aspects, such as adequate control of chronic diseases, prevention of cognitive deficits, encouraging the practice of physical activities and collaboration of family members and caregivers to promote the autonomy of the elderly. The results support the establishment of indicators to improve the monitoring and the planning of actions focused on the outpatient context, enabling the organization of intervention priorities and the creation of preventive measures.